DENDROBIUM AND PHALAENOPSIS GERMPLASMS CONSERVATION BY CLONING TECNOLOGY - soetopo, lita; Purnamaningsih, Sri Lestari (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
The present studies were focused on regeneration of dendrobioum and phalaenopsis species through cloning technique as a means for ex situ conservation of protected or valuable orchids germplasms.Experimental results indicated the growth and development of adventive shoot tip explant dendrobium was as followed : high survival percentage for explant with green color was showed by D. racianum, followed by D. laxiflorum, D. pseudoconantum, D. strebloceras, D. lineale and D. veratrifolium. But plantlets regeneration occurred only on D. pseudoconantum and D. strebloceras . Explant regeneration from seed derived protocorm-like bodies on D. spectabile occurred 40 days after inoculation and after subcultured. High survival percentage of explant from floral stalk shoot was showed by P. amabilis. There was several plantlets survived at acclimatitation. Explant regeneration from seed derived protocorm-like bodies on P. hieroglypha occurred 40 days after inoculation and after subcultured.It was suggested that for ex situ conservation on certain species of dendrobium and phalaenopsis in the category of rare or valuable germplasms, cloning technology could be applied by using explant from adventive shoot tip, floral stalk buds and seed derived protocorm-like body explant for vegetative seed multiplication. Keywords : Orchid, conservation, germplasms in vitro culture.